2010
DOI: 10.1016/j.ejcnurse.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of statins on mood: a review of the literature

Abstract: This review found conflicting evidence of a relationship between statins and mood. Further research is recommended in particular with older, female and lower socioeconomic samples. However, nurses should be alert to the risk and ready to intervene in cases of mood disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 52 publications
4
40
0
3
Order By: Relevance
“…The reason for the positive association between symptom severity and HDL‐C is unclear, particularly since HDL‐C has anti‐inflammatory properties 46 and recent evidence suggests that use of cholesterol improving medication is associated with improved mental health 47. Nevertheless, the findings are consistent with previous research demonstrating that depressive symptoms and suicidality are associated with lowered total cholesterol and higher HDL‐C,48, 49 although heterogeneity between studies is high and the effect is not always observed 50, 51. Overall, people with psychopathology may have a more nuanced risk pattern across metabolic syndrome components, rather than increased risk of metabolic abnormalities across the board.…”
Section: Discussionsupporting
confidence: 80%
“…The reason for the positive association between symptom severity and HDL‐C is unclear, particularly since HDL‐C has anti‐inflammatory properties 46 and recent evidence suggests that use of cholesterol improving medication is associated with improved mental health 47. Nevertheless, the findings are consistent with previous research demonstrating that depressive symptoms and suicidality are associated with lowered total cholesterol and higher HDL‐C,48, 49 although heterogeneity between studies is high and the effect is not always observed 50, 51. Overall, people with psychopathology may have a more nuanced risk pattern across metabolic syndrome components, rather than increased risk of metabolic abnormalities across the board.…”
Section: Discussionsupporting
confidence: 80%
“…Statins are strong HMGR inhibitors widely prescribed in therapies against hypercholesterolemia and their benefits in preventing atherosclerosis and other cardiovascular diseases are incontrovertible. Recently, it has been reported that high-dose statin treatment induces effects in emotional, learning, and memory processes (Kilic et al, 2012;Douma et al, 2011;Baytan et al, 2008;While and Keen, 2010). However, the role of the MVA biosynthetic pathway in the modulation of emotional behavior and cognitive performance is still unclear because of the lack of systematic studies on the causal link between the activation of this metabolic pathway and behavioral and cognitive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Possible effects of statins on mood have been reviewed recently [8]. The authors reviewed effects of statins on a variety of mood states namely depression, anxiety, anger, hostility, fatigue, confusion and vigour.…”
Section: Concerns About Statinsmentioning
confidence: 99%